Inggris - Apdelmi; Reka Seprina (IAIN Madura, 2026)
This study aims to explore the potential of Berhala Island as a historical educational tourism destination for the public, students, university students, and teachers. Berhala Island is an entry point to the Riau Islands Province and has historical and cultural significance. The uniqueness of this island lies in its historical heritage related to Jambi Province. The research method used was descriptive qualitative, with data collected through interviews, observations, and documentation. The results of the study indicate that Berhala Island possesses historical relics connected to the origins of the Jambi kingdom, namely the Tomb of Datuk Paduko Berhala. In addition, the island also preserves evidence of the Japanese occupation in Jambi, such as Japanese cannons, kitchens, and bunkers. These historical remains can serve as valuable educational tourism attractions. Furthermore, the natural beauty of Berhala Island supports the development of experience-based history learning and the preservation of local culture for younger generations and the wider community.